2013
DOI: 10.1103/physrevb.87.174514
|View full text |Cite
|
Sign up to set email alerts
|

Field-angle-resolved anisotropy in superconducting CeCoIn5using realistic Fermi surfaces

Abstract: We compute the field-angle-resolved specific heat and thermal conductivity using realistic model band structure for the heavy-fermion superconductor CeCoIn5 to identify the gap structure and location of nodes. We use a two-band tight-binding parametrization of the band dispersion as input for the self-consistent calculations in the quasiclassical formulation of the superconductivity. Systematic analysis shows that modest in-plane anisotropy in the density of states and Fermi velocity in tetragonal crystals sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…The difference between An et al's C/T work's conclusions about the correct nodal direction (in the [110] direction) and previous somewhat higher temperature C/T (,H) work (Aoki et al [224]) which incorrectly assigned dxy pairing with nodes in the [100] direction is the inversion of the nodal/antinodal directions with lowering temperature in the superconducting state as theoretically explained by Vorontsov and Vekhter [77]. See also Das et al [225].…”
Section: Cecoin5mentioning
confidence: 91%
“…The difference between An et al's C/T work's conclusions about the correct nodal direction (in the [110] direction) and previous somewhat higher temperature C/T (,H) work (Aoki et al [224]) which incorrectly assigned dxy pairing with nodes in the [100] direction is the inversion of the nodal/antinodal directions with lowering temperature in the superconducting state as theoretically explained by Vorontsov and Vekhter [77]. See also Das et al [225].…”
Section: Cecoin5mentioning
confidence: 91%
“…While a variety of experimental probes have reported evidence for the existence of nodes [9][10][11][12] , a sign change of the superconducting (SC) order parameter along the Fermi surface 13,14 , and spinsinglet pairing 11,12 , theoretical efforts [20][21][22][23][24][25][26] to provide a quantitative or even qualitative explanation for the properties of the superconducting state in CeCoIn 5 have been hampered by insufficient insight into the material's complex electronic bandstructure 16 . This situation, however, has recently changed due to a series of groundbreaking scanning tunneling spectroscopy (STS) experiments [33][34][35] which have yielded unprecedented insight into the electronic structure of the superconducting state, providing strong evidence for its unconventional d x 2 −y 2 -wave symmetry.…”
mentioning
confidence: 99%
“…CeCoIn 5 1 has long been considered the "hydrogen atom" of heavy fermion superconductivity [2][3][4][5][6][7][8] , and much experimental [9][10][11][12][13][14][15][16][17][18][19] and theoretical effort [20][21][22][23][24][25][26][27] has focused on illuminating its unconventional properties [28][29][30][31][32] , and the microscopic mechanism underlying the emergence of superconductivity. While a variety of experimental probes have reported evidence for the existence of nodes [9][10][11][12] , a sign change of the superconducting (SC) order parameter along the Fermi surface 13,14 , and spinsinglet pairing 11,12 , theoretical efforts [20][21][22][23][24][25][26] to provide a quantitative or even qualitative exp...…”
mentioning
confidence: 99%
“…However, there is a longstanding experimental discrepancy in the angular dependence of in-plane H c2 : some experiments found that the maxima of H c2 are along the [110] direction 35 , whereas other experiments observed the maxima of H c2 along the [100] direction 9,36,37 . This discrepancy is regarded as an open puzzle in this field 9,38 , and prevents us from reaching a final consensus on the precise gap symmetry of CeCoIn 5 .…”
Section: Introductionmentioning
confidence: 99%